Francis Alÿs. The Nature of the Game - Claes, Gerard-Jan; Symons, Stéphane (Leuven University Press, 2023)
The first multidisciplinary analysis of one of the most impactful and popular contemporary artworks of recent years. In 1999, a short video of a solitary boy kicking an empty bottle up a hill in Mexico City became the first instalment of Children's Games, a series of works by artist Francis Alÿs (b. Antwerp, 1959). The ongoing project, which now numbers around thirty-five works, has gradually given shape to an extensive collection of videos of children at play. For almost twenty-five years, Alÿs and his collaborators Félix Blume, Julien Devaux, and Rafael Ortega have been travelling around the world to document the distinctive ways in which children interact with each other and their physical environment. They have gone from remote villages in the Democratic Republic of the Congo, Afghanistan, Venezuela, and Nepal to the mountains of Switzerland and metropoles like Hong Kong and Paris, but have also visited the war-torn city of Mosul in Iraq, the border between Mexico and the United States, and the strait of Gibraltar that divides Africa and Europe. The resulting images are standing proof of the seriousness of play and of children's stunning powers of resilience in the face of conflict. This volume provides a multidisciplinary perspective to the many layers of Children's Games. It includes an interview with Francis Alÿs and Rafael Ortega, a series of essays by well-known scholars and art critics, curatorial statements, and a logbook related to the presentation of Children's Games at the Venice Biennale of 2022. Contributors: Francis Alÿs (artist), Gerard-Jan Claes (filmmaker, artistic director of Sabzian), Tim Ingold (anthropologist, University of Aberdeen), Zeynep Kubat (art historian, curator and writer), Karen Lang (art historian, Royal Society of Arts), Rafael Ortega (artist), Rodrigo Perez de Arce (architect, Pontificia Universidad Católica de Chile), Juan Martín Pérez García (Network for the Rights of Children in Mexico (REDIM)), Giulio Piovesan (journalist and photographer), John Potter (media education, University College London), Virginia Roy (curator at the University Museum of Contemporary Art of the National Autonomous University of Mexico), Stéphane Symons (professor of philosophy, KU Leuven), Hilde Teerlinck (Han Nefkens Foundation /curator of the Belgian Pavilion at the Venice Art Biennale 2022). Ebook available in Open Access.